Ophthalmologic Psychophysical Tests Support OCT Findings in Mild Alzheimer's Disease. (27th May 2015) - Salobrar-Garcia, Elena; de Hoz, Rosa; Rojas, Blanca; Ramirez, Ana I.; Salazar, Juan J.; Yubero, Raquel; Gil, Pedro; Triviño, Alberto; Ramirez, José M.
Abstract : Purpose . To analyze in mild Alzheimer's disease (MAD) patients, GDS-4 (Reisberg Scale), whether or not some psychophysical tests (PTs) support OCT macular findings in the same group of MAD patients reported previously. Methods . Twenty-three MAD patients and 28 age-matched control subjects with mean Mini Mental State Examination of 23.3 and 28.2, respectively, with no ocular disease or systemic disorders affecting vision were included. Best-corrected visual acuity (VA), contrast sensitivity (CS) (3, 6, 12, and 18 cpds), color perception (CP), and perception digital test (PDT) were tested in one eye of each patient. Results . In comparison with the controls, MAD patients presented (i) a significant decrease in VA, PDT, and CS for all spatial frequencies analyzed, especially the higher ones, and (ii) a significant increase in unspecific errors on the blue axis (P < 0.05 in all instances). In MAD patients, a wide aROC curve was plotted in all PTs. Conclusions . In MAD, CS, VA, and the tritan axis in CP were impaired. The PTs with the greatest predictive value are the higher spatial frequencies in CS and tritan unspecific errors in CP. PT abnormalities are consistent with the structural findings reported in the same MAD patients using OCT.